Can Wordwall Application Improve Students’ Arabic Mastery? - Muhammad Nur Kholis; Laily Fitriani; Riski Gunawan; Moh. Sholeh Afyuddin; Nuryani Nuryani (Universitas Islam Negeri Palangka Raya, 2022)
Wordwall is one of the applications that is widely used in learning foreign languages. In Arabic language learning, wordwall is still studied and researched only at the level of qualitative research or only at describing its application process in learning. However, no one has tested it in the framework of the experiment to see its effectiveness. This study investigates the effectiveness of learning Arabic using Wordwall based on learning outcomes. It uses a pre-experimental One-Group Pretest-Posttest Design. It recruited 72 first-year students in the Arabic language reinforcement program under UIN Raden Mas Said Surakarta Language Development Center. The primary data is collected using pretest and posttest results, and then the results are analyzed using the t-test. Findings revealed that using Wordwall in the Arabic learning process effectively improved the student's Arabic skills.